Pembuatan Dan Aktivitas Antibakteri Yogurt Hasil Fermentasi Tiga Bakteri (Lactobacillus bulgaricus, Streptococcus thermophilus, Lactobacilus acidophilus) - Kamara, Dian S.; Rachman, Saadah D.; Pasisca, Ridya Widya; Djajasoepana, Sadiah; Suprijana, O.; Idar, Idar; Ishmayana, Safri (Al-Kimia, 2016)
Exploitation of synthetic antibiotics compounds not only have positive effect for human, but also have side effect that can be unfavorable, therefore many researches are being conducted to find natural antibiotics compounds that are safer. Lactic acid bacteria has the abilitytoproduce antibacterial compound when used in fermentation process.For example, Lactobacillus acidophilus produces acidophilin and acidolin. The main purpose of the present study is to investigate antibacterial activity of yogurt fermented with mixed bacterial culture of L. bulgaricus, S. thermophilus and L. acidophilus against Escherichia coli (representing Gram negative bacteria) and Bacillus subtilis (representing Gram positive bacteria). The antibacterial activity of the yogurt at three different time points (5, 7 and 9 hours) were examined. We also investigate the fermentation parameters of the yogurt production. The results of the present study indicate that the crude yogurt extract has antibacterial activity, where the highest activity was observed at 7 hour of incubation, resulting 0.35 and 0.30 cm of clear zone against E. coli and B. subtilis, respectively. It is most likely that the compound is non protein compound.